2013
DOI: 10.1007/s12013-013-9740-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure

Abstract: We sought to study the clinical efficacy of various combined blood purification techniques in patients with non-viral acute liver failure complicated by multiple organ dysfunction syndrome (MODS). For this purpose, 19 patients diagnosed of mid- or late-stage liver failure with MODS score-4 were randomly divided into 3 treatment groups of PE+HP+CVVHDF, PE+CVVHDF, and HP+CVVHDF, respectively. Pre- and post-treatment heart rate (HR), mean arterial pressure (MAP), arterial blood gases (pH, PaO2, and PaCO2), hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Unfortunately, this study also did not examine ammonia or creatinine levels. A total of 51 sessions were completed between 19 patients 55 . This study showed that when plasma exchange was combined with hemodiafiltration, it was more effective than when combined with hemoperfusion and all three treatments together were the most effective 55 …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Unfortunately, this study also did not examine ammonia or creatinine levels. A total of 51 sessions were completed between 19 patients 55 . This study showed that when plasma exchange was combined with hemodiafiltration, it was more effective than when combined with hemoperfusion and all three treatments together were the most effective 55 …”
Section: Resultsmentioning
confidence: 88%
“…The study showed that there was lower citrate and IL-18 levels but not IL-6 levels. 9 Li et al 55 examined 19 patients with multiple organ dysfunction syndrome and liver failure. This study also did not examine hemodiafiltration individually but compared it alongside plasma exchange and hemoperfusion.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the replacement fluid in TPE would contain albumin, which would further convert unconjugated bilirubin to conjugated bilirubin. Therefore, the innate process of TPE would effectively remove bilirubin as well as bind excess bilirubin through interaction with albumin resulting in effective management of hyperbilirubinemia which is well supported in the literature . Additionally, the combination of TPE with molecular adsorbent recirculating system (MARS) can more effectively reduce bilirubin levels.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, the HA330 macroporous adsorption resin used in HP has a relative specificity for systemic inflammatory response syndrome, acute respiratory distress syndrome, sepsis and acute necrotic pancreatitis; thus, it can be used to remove the protein-bound toxins and toxic factors. PE is another blood purification modality that can remove antibodies, immune complexes, and toxins as well as replenish coagulation factors and other bioactive substances by using fresh frozen plasma [17,18] . However, PE alone cannot efficiently remove the medium and small toxin particles.…”
Section: Discussionmentioning
confidence: 99%